ANALISIS JARINGAN CPM-PERT UNTUK OPTIMALISASI PEMBANGUNAN WAHANA PERMAINAN BENGKEL SUROBOYO CARNIVAL (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2013)
Suroboyo Carnival is a interactive amusement park project. This amusement park required dynamic planning and scheduling system to produce the best possible results. This project must be to adapt with changing conditions and make necessary changes in the plan and schedule. PERT and CPM are used to analysis of project scheduling problems. CPM has single time estimate and PERT has three time estimates for activities and uses probability theory to find the chance of reaching the scheduled time. This paper used simple hypothetical to solve time schedulling with CPM-PERT technique. It expected duration is simulated and computed using the software package of POM for Windows. The result can facilitate the application of optimalization in CPM-PERT technique correctively and flexibly.